Upaya Pemerintah Mempertahankan Posisi Sebagai Regulator Utama Penyiaran di Indonesia - Nina Mutmainnah (Jurnal Komunikasi)
This study aims to examine the attitude of the government to maintain its position in the broadcast media system. Using the case study method, the author examined series of regulation of broadcasting, minutes of meeting, and media reporting on two broadcasting bill -- the  Broadcasting Act of 1997, the Broadcasting Act of 2002—and the revision of the Broadcasting Act on two parliament periods (2009 - 2014 and 2014 - 2019). The results of this study indicate the government is trying to maintain its position as the main regulator of broadcasting. Even though the Broadcasting Act of 2002 stipulates the Indonesian Broadcasting Commission (KPI) as the main regulator, the government still strives to be a broadcast regulator by giving birth to regulations that restore its position as the main regulator. This can be seen from the different standpoints in the two parliament periods in the revision of the Broadcasting Law: The 2009-2014 parliament strengthened the authority of the KPI, while the 2014-2019 parliament downgraded the KPI's authority and made the government the main regulator. The broadcast industry from the start wanted the government as the main regulator, while civil society rejected the government as the main regulator of broadcasting.